Analisis gambaran histogramdan densitas kamar pulpa pada gigi suspek pulpitis reversibel dan ireversibel dengan menggunakan radiografi cone beam computed tomography (Histogram and density analysis of irreversible and reversible pulpitissuspected tooth using cone beam computed tomography radiography) - Lusi Epsilawati; Suhardjo Sitam; Sam Belly; Fahmi Oscandar (Journal of Dentomaxillofacial Science, 2014)
Inflammation of the pulp is most common and difficult to diagnose. For it radiographs is necessary. One attempt to do is to assess its histogram and density. Radiography equipment that has the ability to analyze is cone beam computedtomography (CBCT). The purpose of this study is to analyze radiograph of the pulp chamber histogram: peak value,grayscale and trends, as well as the density on the condition reversible and irreversible pulpitis condition. The populationof this descriptive study is secondary data of CBCT-3D radiographs during 2012-2013. Selected sample of 75 data isreversible pulpitis, irreversible pulpitis 80 data, as well as 20 normal condition data as control. Data were analyzed byone way ANOVAand are presented in tables and graphs. The results showed that the value of the histogram under normalconditions showeda different significance for both the peak value of the reversible or irreversible pulpitis (pï€ = 0.01). It isdifferent with a grayscale value, showed no significant different between normal with reversible pulpitis (p =0.997) and significantly different between normal and pulpitis reversible against pulpitis irrebversible (pï€ = 0.03-0.01). There is a growing trend change is on the right direction of reversible and irreversible pulpitis. It was concluded that the irreversiblepulpitis, density and histogram shows the direction of more luscent compared with normal and reversible pulpitisconditions.